ENERGY EFFICIENCY COMPETENCE OF A SPECIALIST IN THE CONSTRUCTION INDUSTRY: ANALYSIS OF DOMESTIC AND FOREIGN STUDIES (Innovative professional education, 2025)
This article analyzes domestic and foreign research on the formation of energy efficiency competence among future specialists in the construction industry. The main publications of Ukrainian and foreign scientists are reviewed, successful projects and programs on energy efficiency are evaluated, and approaches to the formation of energy efficiency competence in different countries are compared. Special attention is paid to the technical, practical, managerial, and communication skills necessary for effective energy resource management
Keywords: energy efficiency, competence, construction industry, energy saving, renewable energy sources, sustainable development, energy project management